Towards workers' environmental rights: An analysis of EU labour and environmental law - Kalina Arabadjieva; Paolo Tomassetti (European Trade Union Institute (ETUI), 2024)
Building on the ongoing discussion on the labour-environment nexus in labour law and other areas of scholarship, in this paper we systematically analyse EU legal instruments in the areas of labour law and environmental law, seeking to assess how these normative and policy domains are related to each other. We draw on the explicit and implicit intersections between these two domains when it comes to relevant EU legislation, in order to identify and conceptualise early examples of what we call 'workers' environmental rights'. These rights include individual and collective rights whose exercise contributes simultaneously to labour and environmental sustainability. Where such 'workers' environmental rights' are not explicitly set out in legislation, we provide insights into how they could be construed via judicial interpretation, as well as on how they could be integrated in future EU and national legislation through statutory provisions or collective agreements.
Keywords: 330